Polymorphisms of the 5-HT2A receptor gene and clinical response to olanzapine in paranoid schizophrenia. - Olajossy-Hilkesberger, L; Godlewska, B; Schosser-Haupt, A; Olajossy, M; Wojcierowski, J; Landowski, J; Marmurowska-Michałowska, H; Kasper, S (2011)
BACKGROUND: 5-HT2A receptor is strongly implicated in the mode of action of atypical antipsychotic drugs. The aim of the study was to investigate whether the 5-HT2A receptor gene's polymorphisms (His452Tyr and T102C) have an influence on the response to olanzapine in patients with schizophrenia. METHODS: We studied 99 Caucasian schizophrenia patients treated with olanzapine. Psychopathology was measured before and after 6 weeks of treatment. Clinical improvement was quantified as change in Positive and Negative Syndrome Scale (PANSS) total scores and subscores as shown by percentage improvement below the baseline score. The clinical response to antipsychotic treatment was defined as 30% improvement from baseline in PANSS scores. RESULTS: The His/Tyr polymorphism was significantly associated with a percentage improvement in PANSS positive symptom subscore (better response in His/His homozygotes; p<0.05) after treatment with olanzapine. As for the T102C polymorphism, a better response in terms of PANSS positive subscore improvement was observed for C/C homozygotes (p<0.01). A significant association of 5-HT2A genotype distribution of the T102C polymorphism with a categorical measure of response, but only in terms of PANSS positive symptom subscores, was observed (p<0.01). CONCLUSIONS: Variations in the 5-HT2A receptor gene may influence individual and particularly positive symptom response to olanzapine.